Oral Cancer Stem Cell-Derived Small Extracellular Vesicles Promote M2 Macrophage Polarization and Suppress CD4+ T-Cell Activity by Transferring UCA1 and Targeting LAMC2 - Lan Wu; Sai Ye; Yilin Yao; Chenping Zhang; Wei Liu (Stem Cells International)
Cancer-derived small extracellular vesicles (sEVs) are emerging as crucial mediators of intercellular communication between cancer cells and M2-tumor-associated macrophages (M2-TAMs) via transferring lncRNAs. We previously reported that miR-134 blocks the expression of its targeting protein LAMC2 via the PI3K/AKT pathway and inhibits cancer stem cell (CSC) migration and invasion in oral squamous cell carcinoma (OSCC). This study hypothesize that OSCC-CSC-derived small extracellular vesicles (OSCC-CSC-sEVs) transfer a ceRNA of miR-134 and consequently promote M2 macrophage polarization by targeting LAMC2 via the PI3K/AKT pathway through in vitro and in vivo experiment methods. The results showed that sEVs derived from CD133+CD44+ OSCC cells promoted M2 polarization of macrophages by detecting several M2 macrophage markers (CD163, IL-10, Arg-1, and CD206+CD11b+). Mechanistically, we revealed that the lncRNA UCA1, by binding to miR-134, modulated the PI3K/AKT pathway in macrophages via targeting LAMC2. Importantly, OSCC-CSC-sEV transfer of UCA1, by targeting LAMC2, promoted M2 macrophage polarization and inhibited CD4+ T-cell proliferation and IFN-γ production in vitro and in vivo. Functionally, we demonstrated that M2-TAMs, by transferring exosomal UCA and consequently targeting LAMC2, enhanced cell migration and invasion of OSCC in vitro and the tumorigenicity of OSCC xenograft in nude mice. In conclusion, our results indicated that OSCC-CSC-sEV transfer of UCA1 promotes M2 macrophage polarization via a LAMC2-mediated PI3K/AKT axis, thus facilitating tumor progression and immunosuppression. Our findings provide a new understanding of OSCC-CSC molecular mechanisms and suggest a potential therapeutic strategy for OSCC through targeting CSC-sEVs and M2-TAMs.